Hardness Analysis Of Hard Facing In Shield Metal Arc Welding (Smaw) Welding Process For Manufacturing Excavators Bucket Teeth Using Hot Rolled Plate Ks 440 Material - Rerung, Oktovianus Dharma (Universitas Muhammadiyah Metro, 2024)
In the context of increasing development across regions, the demand for adequate heavy equipment to support construction has become crucial. Wheel loaders and excavators are commonly used heavy equipment for various tasks, including excavation, material handling, and mining operations. The bucket, a crucial component responsible for digging and lifting materials in these machines, often experiences wear and breakage during operation, particularly in the bucket teeth – the claw-like structures at the bucket's end. This study focuses on the design and improvement of bucket teeth using the hard facing technique, a welding process utilizing wear-resistant electrodes. The choice of material, Hot Rolled Plate Ks 440, combined with proper hard facing electrode selection, aims to enhance wear resistance and prolong the lifespan of bucket teeth. The research incorporates Shield Metal Arc Welding (SMAW) for its simplicity and effectiveness. Experimental results, analyzed using Analysis of Variance (ANOVA), reveal significant influences of cooling and electrode factors on hardness (measured in HRC) of the bucket teeth. The combination of welding electric current, electrode type, and cooling method impacts hardness significantly. The best-performing bucket teeth, with a mean hardness of 49.459 HRC to 50.778 HRC, meet or exceed the standards set by AISI 4130 steel. The study aligns with heat treatment theories for surface hardness improvement in steel, showcasing the effectiveness of the proposed design and hard facing approach.